New Architecture in Wood : Forms and Structures - Lennartz, Marc Wilhelm (Birkhäuser, 2015)
Timber: the old raw material and building material returns. Based on 24 international projects, the book provides an overview of the range of possibilities in wood construction today. Texts, images, and plans document the architectural and constructive qualities of contemporary timber structures from the conceptual design to the structure in detail.